THE DEVELOPMENT MODEL OF MODERN CHINA: ESTIMATES, DISCUSSIONS, FORECASTS / ED. BY ALEXEI D. VOSKRESSENSKI. MOSCOW: STRATEGICHESKIYE IZYSKANIYA, 2019.736 P. - article Editorial (Сравнительная политика, 2019)
.